Pengaruh Model Pembelajaran Kooperatif tipe Teams Games Tournament (TGT) Terhadap Motivasi Belajar Matematika Siswa Kelas IV SD Negeri 12 GU - Rismayani Armin; Astuti Astuti (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
The purpose of this research was to determine the effect of the cooperative learning mdel type teams games tournament(TGT) on the mathematics learning motivation of fourth grade students at SD Negeri 12 Gu.This research was a quantitative research with a quasi-experimental design method. The population in this research were all fourth grade students of SD Negeri 12 Gu in the odd semester of the 2021/2022 academic year which consisted of 2 classes with a total of 44 students who where also used as samples using total sampling technique. This serearch data collection using a questionnaire. The results of this researh showed the based on the results of descriptive analysis, the average value of the increase in the results of the experimental class mathematics learning motivation quetionnaire was 25.00; the average increase in the results of the control class mathematics leraning motivation questionnaire was 16.85; and based on the results of inferential analysis by looking at the normality test, the significant value of the questionnaire on motivation to learn mathematics in the experimental class was 0.200 and the control class was 0.200, while the homogeneity test showed that the value of the questionnaire on students motivation to learn mathematics in both classes was 0.338>0.05. So that it could be said that the two classes were normally distributed and homogeneus. By using the t-test, it was known that is was significant0.037<0,050, which meant that H0 was rejected. So that it was concluded that there was an effect of the cooperative learning model of the Teams Games Tournament (TGT) type on the mathematics learning motivation of fourth grade students at SD Negeri 12 Gu.